Scientific production on workplace bullying/harassment in dissertations and theses in the Brazilian scenario - Isabelle Cristinne Pinto Costa; Solange Fátima Geraldo da Costa; Cristiani Garrido de Andrade; Regina Célia de Oliveira; Fátima Maria da Silva Abrão; Carlos Roberto Lyra da Silva (SciELO, 2015)
OBJECTIVE To analyze scientific production about workplace bullying and harassment in dissertations and theses in Brazil, with emphasis on the year of publication; educational institution; area of knowledge; professional and academic background of the authors; keywords used; and concept map organization. METHOD Bibliometric study with a quantitative approach with a sample consisting of 57 papers, 5 theses and 52 dissertations, published between 2002 and 2012. RESULTS It was found that 2012 was the year with the highest number of publications in this topic area. The region that stood out was the Southeast. The institution with the highest number of publications was the Federal University of Santa Catarina. There was a predominance of dissertations and most publications were produced by researchers focused on a multidisciplinary perspective. CONCLUSION Expanding the views regarding bullying in order to disseminate scientific production was proposed, promoting further advancement of debates and raising pertinent questions.